Treatment of early‐stage mycosis fungoides: results from the PROspective Cutaneous Lymphoma International Prognostic Index (PROCLIPI) study. (1st April 2021) - Quaglino, P.; Prince, H.M.; Cowan, R.; Vermeer, M.; Papadavid, E.; Bagot, M.; Servitjie, O.; Berti, E.; Guenova, E.; Stadler, R.; Querfeld, C.; Busschots, A.M.; et al.
Summary: Background: The PROspective Cutaneous Lymphoma International Prognostic Index (PROCLIPI) study is a prospective analysis of an international database. Here we examine front‐line treatments and quality of life (QoL) in patients with newly diagnosed mycosis fungoides (MF). Objectives: To identify (i) differences in first‐line approaches according to tumour‐nodes‐metastasis‐blood (TNMB) staging; (ii) parameters related to a first‐line systemic approach and (iii) response rates and QoL measures. Methods: In total, 395 newly diagnosed patients with early‐stage MF (stage IA–IIA) were recruited from 41 centres in 17 countries between 1 January 2015 and 31 December 2018 following central clinicopathological review. Results: The most common first‐line therapy was skin‐directed therapy (SDT) (322 cases, 81·5%), while a smaller percentage (44 cases, 11·1%) received systemic therapy. Expectant observation was used in 7·3%. In univariate analysis, the use of systemic therapy was significantly associated with higher clinical stage (IA, 6%; IB, 14%; IIA, 20%; IA–IB vs. IIA, P < 0·001), presence of plaques (T1a/T2a, 5%; T1b/T2b, 17%; P < 0·001), higher modified Severity Weighted Assessment Tool (> 10, 15%; ≤ 10, 7%; P = 0·01) and folliculotropic MF (FMF) (24% vs. 12%, P = 0·001). Multivariate analysis demonstrated significant associations with the presence of plaques (T1b/T2b vs. T1a/T2a, odds ratio 3·07) and FMF (odds ratio 2·83). The overall response rate (ORR) to first‐line SDT was 73%, while the ORR to first‐line systemic treatments was lower (57%) ( P = 0·027). Health‐related QoL improved significantly both in patients with responsive disease and in those with stable disease. Conclusions: Disease characteristics such as presence of plaques and FMF influence physician treatment choices, and SDT was superior to systemic therapy even in patients with such disease characteristics. Consequently, future treatment guidelines for early‐stage MF need to address these issues.